PEMBENTUKAN LITERASI, NUMERASI DAN ADAPTASI TEKNOLOGI PADA PROGRAM KAMPUS MENGAJAR PENEMPATAN SMP NEGERI 3 SIDOARJO: (Upaya Menghadapi Era Digital Setelah Pandemi Covid-19 Pada Pendidikan SMP) - Ahmad Sodiq Anashrulloh; Didiek Tranggono (DAS Institute, 2022)
The teaching campus is one of the learning and student programs of the directorate general of higher education, ministry of education, culture, research and technology, called Merdeka Learning Campus Merdeka (MBKM) in the form of teaching assistance to empower students in helping the learning process in junior high schools. placement of SMP Negeri 3 Sidoarjo, East Java Province. Campus teaching activities at placement schools have 3 concepts of literacy, numeracy and technology adaptation. student resources to be useful by contributing and innovating together to help the community. Implementation in campus teaching activities that contribute to helping problems, obstacles and efforts that occur in education. Campus teaching activities provide opportunities for students to participate in teaching and implementing by helping the teaching process in areas determined by the Ministry of Education and Culture, Research and Technology. Helping to increase equity in the quality of education, especially during the post-Covid-19 pandemic. In developing insight and honing thinking skills in working together across fields of science and various backgrounds in solving problems faced. Provide inspiration and motivation to learn for students as well as introduce the cultural diversity of the archipelago, the development of science and technology